Temperature-controlled fabrication of semiconducting polymeric nanocatalysts for selective carbon dioxide conversion and X-ray shielding capacity. (June 2022) - Sakthivel, C.; Prabha, I.
Abstract: The intrinsic semiconducting poly (1-aminoanthraquinone) (PAAQ) was synthesized by simple oxidative polymerization of 1-aminoanthraquinone at 25, 40, and 50 °C in the biphasic system. Seventy percent of perchloric acid was used to enhance the acidity, and 30% of hydrogen peroxide was acted as an oxidant. The synthesized materials were undergone the studies for crystalline nature, surface morphology, optical behavior, and electrochemical potential using X-ray powder diffraction, scanning electron microscopy (SEM), ultraviolet–visible spectroscopy-, fluorescence spectroscopy, Fourier transform infrared spectroscopy, dynamic light scattering, and cyclic voltammetry. The crystalline sizes were found to be 45.47, 45.88, and 45.51 nm, and their band gap energies were 3.89, 3.70, and 3.55 eV at 25, 40, and 50 °C, respectively. The SEM images reveal the formation of well-defined nanocubes with sheets, and the average particles size was 75 nm. Redox peaks in impedance curve proved the efficiency in electrochemical properties of synthesized PAAQ polymers. The PAAQ at 25 °C has showed an optimized catalytic conversion of carbon dioxide to carbon trioxide and the stabilized shielding property against X-ray irradiation during radiation therapy effectively. Highlights: Simple poly (1-aminoanthraquinone) by trouble-free oxidation of 1-aminoanthraquinone with easy reproduction successfully. Optimized crystalline size was confirmed as 45 nm for nanocubes at 25 °C. Emission-excitation at 585, 467 nm for quinine, benzenoid rings and stokes shift maxima for absorption-emission at 118. Efficient and optimistic renovation of carbon dioxide into the valuable products via an unsophisticated and simple route. Electrical conductivity, total dissolved solids, salinity, shielding property against X-ray irradiation was at 25 °C.